Pronunciation Errors of Fricative Sounds Made by English Students - Tiara Azzahra Marpaung; Syafrizal Sabarudin; Mulyadi Mulyadi (Universitas Bengkulu, 2021)
This research aims to identify pronunciation errors position made by students in the English Education Study Program University of Bengkulu and the sound that had the highest error percentage. This research was a descriptive quantitative research. To collect data, the researcher took 19 students from 94 students of the 7th semester in the academic year 2020/2021. The pronunciation test used in this study consisted of 35 words, each of which had one of the seven fricative sounds tested. To analyze the data obtained, researcher used the Audacity application with the help of Google Translate application. Audacity is used to see the amplitude generated from students. Meanwhile, Google Translate is a tool for comparing received pronunciation and pronunciation produced by students. The results of this study revealed that the most pronunciation errors that made by students occurred in the final position when compared the initial and medial. In addition, among seven fricative sounds, / ? / was the highest percentage of errors with 78%. Based on the research results, it can be concluded that the students' pronunciation ability of fricative sounds not affected on the level of the semester is taken but it depends on the position and the fricative sound.